Perbandingan Pendekatan Saintifik antara Kurikulum 2013 dan Pendekatan Burhani dalam Peningkatan Keterampilan Berpikir Tingkat Tinggi pada Mata Pelajaran Fiqih - Nadlir Nadlir; Hanik Yuni Alfiyah (UIN Sunan Ampel Surabaya, 2018)
This article focuses upon the comparison between the Burhani and the 2013 Curriculum scientific approaches in improving high order thinking skills in Fiqh subjects. Two different group of 18 five-grade students of MI Haji Hasyim Babat Jerawat Pakal Surabaya are involved for each approaches within the 2016/2017 academic year. The result shows that both Burhani’s and 2013 Curriculum’s scientific approaches are able to increase high-order thinking skills in terms of collecting information, finding links, rearranging, and developing it to answer questions. Based upon thinking-skill mean, group with 2013 Curriculum scientific approach treatment gains higher achievement that that of with Burhani’s, with 82.66:72.13. This result heightens the theory of 2013 Curriculum’s relevance for all school subjects, including Islamic Education.